The Influence of Tax Inspection and Tax Collection on Tax Revenue at KPP Pratama Jakarta Jatinegara - Vicky Amelia; Ade Budi Setiawan; Yoyok Priyo Hutomo (Universitas Muhammadiyah Makassar, 2024)
The purpose of this study is to ascertain how tax audit and tax collection contribute to tax revenue at KPP Pratama Jakarta Jatinegara. The study's participants were KPP Pratama Jakarta Jatinegara tax employees. Ninety-six tax employees from KPP Pratama Jakarta Jatinegara were included in the study's sample. Saturation sampling is the sample technique employed in this study. SPSS was used in this study to process the data using multiple linear regression. The findings demonstrated that KPP Pratama Jakarta Jatinegara's tax revenue was significantly and favorably impacted by tax audits and collections. Furthermore, it is established that tax audits and tax collection have a 51.4% impact on tax revenue based on the coefficient of determination (R2) test results. However, other factors not covered in this study have an impact on the remaining percentage (100% - 51.4% = 48.6%).